Distributed generation: A review of factors that can contribute most to achieve a scenario of DG units embedded in the new distribution networks. (June 2016) - Colmenar-Santos, Antonio; Reino-Rio, Cipriano; Borge-Diez, David; Collado-Fernández, Eduardo
Abstract: We are witnessing in recent years a significant increase in the penetration of small units of distributed generation on electricity networks, motivated by a higher demand of environmental protection and a gradual process of liberalization on the energy market. In last decade many countries have begun a liberalization process of their electrical systems by opening access to transmission and distribution networks. This has been accompanied by a fast growth in the presence of small generators distributed, of several technologies, many of them based on renewable energy sources. However, there are still technical, economic and regulatory barriers that limit the definitive boost of distributed generation (DG). The increase of connections in many cases, has been based on the philosophy "fit and forget" and capacity of installed DG remains limited by Distribution Network Operators. In this article are reviewed those factors that can contribute most to the necessary evolution of DG, to overcome the current paradigm of renewable distributed generation sources "integrated in a real network", and reach a stage of DG units "embedded in the new distribution networks". To do this, aspects such as, Smartgrids and new information and communications technologies, microgeneration and storage technologies, Active Management Network, multiobjetive planning as an optimization tool for sizing and selection of sites DG, or regulatory issues, are examined along of this article.